2019
DOI: 10.1111/jfbc.12805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and pH on the probiotication ofPunica granatumjuice usingLactobacillusspecies

Abstract: This study was focused on the effects of fermentation temperature and pH on the quality of Punica granatum juice probioticated with Lactobacillus species: Lactobacillus plantarum, Lactobacillus casei, Lactobacillus bulgaricus, and Lactobacillus salivarius. The whole fruit juice of P. granatum which is rich with phytonutrients appeared to be a good probiotic carrier. The probiotication was carried out for 24 hr at 30, 35, and 37°C and pH 2.5, 4.0, and 5.5 under microaerophilic conditions. The results found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
2
12
0
1
Order By: Relevance
“…Few studies have recently reported on the “probiotication” of fruit juice. Mustafa et al [103] investigated the effect of fermentation temperature and pH on the quality of Punica granatum L. juice probioticated with Lb. plantarum , Lb.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have recently reported on the “probiotication” of fruit juice. Mustafa et al [103] investigated the effect of fermentation temperature and pH on the quality of Punica granatum L. juice probioticated with Lb. plantarum , Lb.…”
Section: Resultsmentioning
confidence: 99%
“…The higher the temperature, the lower the fermentation time required to achieve the necessary H+ ion concentration. Similarly, the titratable acidity of the probiotic is also inversely proportional to the temperature at which the fermentation is carried out [ 121 ].stated that the biomass concentration produced by the probiotic bacteria during fermentation is also temperature-dependent. They showed that the Lactobacillus casei species showed higher biomass concentration than other lactobacillus species, notably at 35°C and 37°C [ 122 ], showed the effect of temperature on the growth of bacteria and the production of the acid in the goat yogurt probiotic.…”
Section: Fate Of Probiotic Activity During Major Formulationsmentioning
confidence: 99%
“…Numerous studies proved the probiotic properties of Lactobacillus casei NRRL B-1922 and recognized as safe by the European Food Safety and US Food and Drug Authorities (Mani-L opez et al, 2014;Mohamed et al, 2020). It was used as a probiotic strain in the production of Punica granatum juice (Mustafa et al, 2019) and used in milk supplemented with different probiotics (Soto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…, 2020). It was used as a probiotic strain in the production of Punica granatum juice (Mustafa et al. , 2019) and used in milk supplemented with different probiotics (Soto et al.…”
Section: Introductionmentioning
confidence: 99%